Titanium-based metal ceramic spraying powder and preparation method thereof
By using TI (C, N) powder, (TIM) (C, N) the metal ceramic hot spray powder with solid -soluble powder and bonding powder powder, the existing thermal spray powder is resistant to corrosion performance in an acidic or alkaline environment The poor problem realizes the high -resistant corrosion, high temperature and wear resistance of coating, and extend the service life.
Patent Information
- Application Number
- CN202411430401.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-28
AI Technical Summary
The existing thermal spray powder has extremely poor corrosion resistance in acidic or alkaline environments, and the coating is prone to fall off and has a short service life.
The metal ceramic hot spray powder includes Ti (C, N) powder, (TIM) (C, N) the hot spray of metal ceramics with solid soluble powder and bonding powder. The bonding phase is used to improve the corrosion resistance and wear resistance of the coating.
It significantly improves the corrosion resistance, high temperature and wear resistance of the spray coating, extended the service life, and enhanced the binding force of the coating and the matrix.
Smart Images

Figure CN119372573A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of spray powders, and in particular to titanium-based metal ceramic spray powders and a preparation method thereof. Background Art
[0002] Thermal spraying technology is a processing technology that uses a heating and melting method to heat the material to be sprayed (solid materials such as powder or filament) to a molten or semi-molten state, and then atomizes and accelerates it through a spraying device and stacks it on the surface of the substrate material. Thermal spraying is a technology that uses a heat source to heat the spray material to a molten or semi-melted state, atomizes it with a high-speed airflow and sprays it onto the surface of the substrate to form a coating. WC-Co series thermal spray powders have good strength and excellent toughness, but the corrosion resistance and wear resistance of the coating are usually low, and the corrosion resistance of its single Co bonding phase is extremely poor in acidic or alkaline environments. In addition, because WC series spray powders have a good affinity for metals, the coating is prone to adhesion to the workpiece during operation, which in turn makes the coating have low bonding strength, insufficient corrosion resistance and high temperature resistance, resulting in coating shedding and reduced service life. Summary of the invention
[0003] In view of this, the present application provides a metal ceramic thermal spray powder and a preparation method thereof, aiming to improve the problems of existing thermal spray powders such as low corrosion resistance and wear resistance, easy detachment of the coating, and short service life.
[0004] The embodiment of the present application is implemented as follows: the metal ceramic thermal spraying powder includes Ti(C,N) powder, (TiM)(C,N) solid solution powder, and bonding phase powder, wherein M includes at least one of the elements W, Mo, Cr, V, Zr, Ta, and Nb.
[0005] Optionally, in some embodiments of the present application, the bonding phase powder includes one or more elements of Co, Ni, Mo, and Cr.
[0006] Optionally, in some embodiments of the present application, the Fsss particle size of the Ti(C,N) powder is not greater than 4.0 microns; and / or
[0007] The (TiM)(C,N) solid solution powder has a Fsss particle size of not more than 4.0 microns; and / or
[0008] The Fsss particle size of the binder phase powder is no greater than 4.0 microns.
[0009] Optionally, in some embodiments of the present application, the titanium-based metal ceramic spray powder includes, by mass percentage, 35% to 75% Ti(C,N) powder, 10% to 20% (TiM)(C,N) solid solution powder, and 10% to 50% bonding phase powder.
[0010] Accordingly, the present application also provides a method for preparing a metal ceramic thermal spray powder, comprising:
[0011] Providing a mixed slurry, the mixed slurry comprising Ti(C,N) powder, (TiM)(C,N) solid solution powder, and a binder phase powder;
[0012] Spray granulate the mixed slurry to obtain pre-solidified precursor powder;
[0013] The pre-solid solution precursor powder is subjected to a heating and degreasing stage, a vacuum sintering stage and a cooling stage in sequence to obtain a titanium-based metal ceramic block;
[0014] The titanium-based metal ceramic spray powder is obtained by crushing and screening.
[0015] Optionally, in some embodiments of the present application, Ti(C,N) powder, (TiM)(C,N) solid solution powder, and binder phase powder are weighed according to the above mass percentages to obtain raw material powder, a dispersant and a molding agent are added to the raw material powder, the mixture is evenly mixed to obtain a prepared raw material, and a mixed slurry is obtained by wet grinding; and / or
[0016] The mixed slurry is placed in a spray tower for spray spheroidization granulation, the inlet temperature of the spray tower is T1, the outlet temperature is T2, the centrifugal atomization speed of the spray spheroidization granulation is v1, the frequency is f, and the pre-solid solution precursor powder is spherical; and / or
[0017] The heating and degreasing stage is carried out according to the preheating, vacuuming, heating and insulation procedures, preheating to T3 temperature, the heating rate does not exceed v2, and the insulation time is t1; vacuuming to below P; heating to T4, the heating rate does not exceed v3, and at T4 temperature, insulation time t2; and / or
[0018] During the vacuum sintering stage, the heating rate does not exceed v4, the heating temperature rises from T4 to T5, and is kept warm for t3 time; the heating rate does not exceed v5, when the sintering temperature reaches T6, it is kept warm for t4 time; the heating rate does not exceed v6, when the sintering temperature reaches T7, it is kept warm for t5 time; the heating rate does not exceed v7, when the sintering temperature reaches T8, it is kept warm for t6 time.
[0019] Optionally, in some embodiments of the present application, the prepared raw materials are added into a grinding carbide or stainless steel ball mill of a ball mill, and a solvent is added and ball milling is performed to obtain a mixed slurry.
[0020] Optionally, in some embodiments of the present application, T1 is 180° C. to 280° C.; and / or
[0021] T2 is 100°C to 130°C; and / or
[0022] v1 is 5500 rpm to 9500 rpm; and / or
[0023] f is between 85 Hz and 180 Hz; and / or
[0024] T3 is 80°C to 200°C; and / or
[0025] v2 does not exceed 10℃ / min; and / or
[0026] t1 is 30 min to 60 min; and / or
[0027] P is less than 10Pa; and / or
[0028] T4 is 280°C to 450°C; and / or
[0029] v3 does not exceed 5℃ / min; and / or
[0030] t2 is 50 min to 120 min; and / or
[0031] T5 is 520°C to 600°C; and / or
[0032] v4 does not exceed 5℃ / min; and / or
[0033] v5 does not exceed 4℃ / min; and / or
[0034] T6 is 600°C to 900°C; and / or
[0035] t3 is 10 min to 90 min; and / or
[0036] t4 is 50 min to 90 min; and / or
[0037] v6 does not exceed 3.5℃ / min; and / or
[0038] T7 is 900°C to 1250°C; and / or
[0039] t5 is 50 min to 150 min; and / or
[0040] v7 does not exceed 3.5℃ / min; and / or
[0041] T8 is 1250°C to 1420°C; and / or
[0042] t6 is 70min~210min.
[0043] Optionally, in some embodiments of the present application, the dispersant includes one or more of dodecylbenzenesulfonic acid, stearic acid and oleic acid; and / or
[0044] The molding agent is one or more of rubber, paraffin and PEG; and / or
[0045] The solvent includes one or more of gasoline, ethylene glycol and hexane.
[0046] Optionally, in some embodiments of the present application, in the mixed slurry, the ratio of solid to liquid is (5-7): (5-3); and / or
[0047] The mass fraction of the dispersant in the total amount of the raw material powder is 0.1% to 0.5%; and / or
[0048] The mass fraction of the molding agent to the total amount of raw material powder is 2.5% to 4.5%; and / or
[0049] The volume mass ratio of the solvent to the total amount of the raw material powder is 280ml / Kg to 500ml / Kg; and / or
[0050] During ball milling, 85% to 90% of the total volume of the solvent is first added, and the remaining solvent is added 8 to 10 hours before the end of ball milling; and / or
[0051] The ball mill is a rolling ball mill or a vertical stirring ball mill, the diameter of the carbide balls is 6.25 mm to 12 mm, the ball-to-material ratio is 2.5:1 to 10:1, the ball milling speed is 68 to 85 rpm, and the ball milling time is 16 h to 90 h.
[0052] In the present application, PEG is polyethylene glycol.
[0053] The titanium-based metal ceramic spray powder of the present application, Ti(C, N) powder is a hard phase, (TiM)(C, N) solid solution powder forms a solid solution phase after spraying, and the bonding phase powder is a bonding phase. The (TiM)(C, N) solid solution powder can effectively improve the wettability of the titanium-based metal ceramic spray powder of the present application, reduce its expansion coefficient, and couple and match the interface between the matrix hard phase and the bonding phase, so that the hard phase and the bonding phase in the titanium-based metal ceramic spray powder of the present application can form mutual diffusion of elements at the interface without violent chemical reaction, thereby preventing the formation of brittle phases and deterioration of interface performance;
[0054] In the present application, in the (TiM)(C,N) solid solution powder, the W element can effectively improve the high-temperature red hardness and wear resistance of the spray layer, Mo can improve the wettability interface of the spray powder, enhance the bonding force between the spray layer and the substrate, and improve the service life, Ta and Nb increase the high temperature resistance of the spray layer, Cr improves the corrosion resistance, and the addition of V and Zr elements can effectively inhibit the grain growth of the spray layer at high temperature. These elements can react and precipitate new ceramic phases during the heat treatment process, control the phase structure, particle size and particle morphology and distribution characteristics of the precipitated ceramic phase, and form a high-temperature composite bonding phase during spraying with the solid solution raw material as the main component added phase. The formation of the corrosion-resistant and high-temperature resistant new phase is beneficial to increasing the bonding force between the spray layer and the substrate, and is beneficial to enhancing the high temperature resistance, wear resistance and corrosion resistance, thereby improving the service life.
[0055] During spraying, the hard phase, solid solution phase and bonding phase are quickly deposited and formed, which can significantly improve the powder application rate during the thermal spraying process, increase the thickness of the deposited layer, improve the density of the coating, and further improve the corrosion resistance of the coating; the addition of multiple bonding phases can effectively improve the overall toughness of the metal ceramic powder and the high temperature performance and corrosion resistance of the coating, effectively increase the density, and promote the mutual diffusion of interface forming elements between the hard phase and the bonding phase, thereby preventing the formation of brittle phases and deteriorating interface performance.
[0056] The prepared titanium-based metal ceramic spray powder has good fluidity and the obtained coating has good stability; the coating formed by the spray powder and the surface of the base metal has strong bonding force, and also has the advantages of excellent comprehensive performance such as corrosion resistance, high temperature resistance, low porosity, high density, and high red hardness.
[0057] In the preparation method of the present application, the purpose of using multi-stage sintering in the heating and degreasing stage is to ensure that the forming agent, dispersant, etc. can be completely eliminated and the purity of the powder components can be ensured; the purpose of using multi-stage sintering in the vacuum sintering stage is to ensure uniform degreasing of the powder, solidify the morphology, and ensure the roundness and uniformity of the spherical powder components; the purpose of controlling the heating rate is to effectively remove the forming agent, dispersant, etc., and in addition, it can prevent the sphere from breaking due to excessive heating of the powder. The entire preparation method is easy to operate and suitable for mass production. The prepared titanium-based metal ceramic spray powder is widely used in surface wear-resistant protection projects in the petroleum, chemical, shipbuilding, machinery, metallurgy, electric power and other industries, as well as various wear-resistant parts and surface strengthening of military components. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0059] Figure 1 It is a flow chart of a method for preparing titanium-based metal ceramic spray powder provided in an embodiment of the present application;
[0060] Figure 2 is a scanning electron microscope image provided in Example 1 of the present application;
[0061] Figure 3 is a scanning electron microscope image provided in Example 4 of the present application;
[0062] Figure 4 is a scanning electron microscope image provided in Example 5 of the present application;
[0063] Figure 5is a scanning electron microscope image provided in Example 6 of the present application;
[0064] Figure 6 is a scanning electron microscope image provided in Example 7 of the present application;
[0065] Figure 7 is a scanning electron microscope image provided in Example 8 of the present application;
[0066] Figure 8 is a scanning electron microscope image provided in Example 9 of the present application;
[0067] Fig. 9 is a scanning electron microscope image provided in Example 10 of the present application;
[0068] Fig.10 is a scanning electron microscope image provided in Example 14 of the present application;
[0069] Fig.11 is a scanning electron microscope image provided in Example 15 of the present application;
[0070] Fig.12 is a scanning electron microscope image provided in Example 18 of the present application;
[0071] Fig.13 This is a scanning electron microscope image provided in Example 19 of the present application. DETAILED DESCRIPTION
[0072] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0073] In this application, further, in the description of this application, the term "including" means "including but not limited to." The terms first, second, third, etc. are used merely as labels and do not impose numerical requirements or establish a sequence.
[0074] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0075] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or several", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0076] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0077] The technical solution of this application is as follows:
[0078] In a first aspect, an embodiment of the present application provides a titanium-based metal ceramic spray powder, including Ti(C,N) powder, (TiM)(C,N) solid solution powder, and a bonding phase powder, wherein M includes at least one of W, Mo, Cr, V, Zr, Ta, and Nb elements.
[0079] The titanium-based metal ceramic spray powder of the present application, Ti(C, N) powder is a hard phase, (TiM)(C, N) solid solution powder forms a solid solution phase after spraying, and the bonding phase powder is a bonding phase. The (TiM)(C, N) solid solution powder can effectively improve the wettability of the titanium-based metal ceramic spray powder of the present application, reduce its expansion coefficient, and couple and match the interface between the matrix hard phase and the bonding phase, so that the hard phase and the bonding phase in the titanium-based metal ceramic spray powder of the present application can form mutual diffusion of elements at the interface without violent chemical reaction, thereby preventing the formation of brittle phases and deterioration of interface performance;
[0080] In the present application, in the (TiM)(C,N) solid solution powder, the W element can effectively improve the high-temperature red hardness and wear resistance of the spray layer, Mo can improve the wettability interface of the spray powder, enhance the bonding force between the spray layer and the substrate, and improve the service life, Ta and Nb increase the high temperature resistance of the spray layer, Cr improves the corrosion resistance, and the addition of V and Zr elements can effectively inhibit the grain growth of the spray layer at high temperature. These elements can react and precipitate new ceramic phases during the heat treatment process, control the phase structure, particle size and particle morphology and distribution characteristics of the precipitated ceramic phase, and form a high-temperature composite bonding phase during spraying with the solid solution raw material as the main component added phase. The formation of the corrosion-resistant and high-temperature resistant new phase is beneficial to increasing the bonding force between the spray layer and the substrate, and is beneficial to enhancing the high temperature resistance, wear resistance and corrosion resistance, thereby improving the service life.
[0081] During spraying, the hard phase, solid solution phase and bonding phase are quickly deposited and formed, which can significantly improve the powder application rate during the thermal spraying process, increase the thickness of the deposited layer, improve the density of the coating, and further improve the corrosion resistance of the coating; the addition of multiple bonding phases can effectively improve the overall toughness of the metal ceramic powder and the high temperature performance and corrosion resistance of the coating, effectively increase the density, and promote the mutual diffusion of interface forming elements between the hard phase and the bonding phase, thereby preventing the formation of brittle phases and deteriorating interface performance.
[0082] The prepared titanium-based metal ceramic spray powder has good fluidity and the obtained coating has good stability; the coating formed by the spray powder and the surface of the base metal has strong bonding force, and also has the advantages of excellent comprehensive performance such as corrosion resistance, high temperature resistance, low porosity, high density, and high red hardness.
[0083] In the preparation method of the present application, the purpose of using multi-stage sintering in the heating and degreasing stage is to ensure that the forming agent, dispersant, etc. can be completely eliminated and the purity of the powder components can be ensured; the purpose of using multi-stage sintering in the vacuum sintering stage is to ensure uniform degreasing of the powder, solidify the morphology, and ensure the roundness and uniformity of the spherical powder components; the purpose of controlling the heating rate is to effectively remove the forming agent, dispersant, etc., and in addition, it can prevent the sphere from breaking due to excessive heating of the powder. The entire preparation method is easy to operate and suitable for mass production. The prepared titanium-based metal ceramic spray powder is widely used in surface wear-resistant protection projects in the petroleum, chemical, shipbuilding, machinery, metallurgy, electric power and other industries, as well as various wear-resistant parts and surface strengthening of military components.
[0084] Furthermore, the bonding phase powder includes one or more elements of Co, Ni, Mo, and Cr.
[0085] Further, the Fsss particle size of the Ti(C,N) powder is not greater than 4.0 microns, for example, it can be 0.1 micron, 0.2 micron, 0.5 micron, 0.8 micron, 1 micron, 1.2 micron, 1.4 micron, 1.6 micron, 1.8 micron, 2 micron, 2.2 micron, 2.5 micron, 2.8 micron, 3 micron, 3.1 micron, 3.2 micron, 3.5 micron, 3.6 micron, 3.8 micron, 4 micron, etc. Within the micron range, the requirements of wear resistance and high temperature corrosion performance can be fully met.
[0086] Further, the Fsss particle size of the (TiM)(C,N) solid solution powder is not greater than 4.0 microns, for example, it can be 0.1 micron, 0.2 micron, 0.5 micron, 0.8 micron, 1 micron, 1.2 micron, 1.4 micron, 1.6 micron, 1.8 micron, 2 micron, 2.2 micron, 2.5 micron, 2.8 micron, 3 micron, 3.1 micron, 3.2 micron, 3.5 micron, 3.6 micron, 3.8 micron, 4 micron, etc. Within the micron range, the deposition effect of the multi-hard phase solid solution phase reinforcement material can be effectively achieved.
[0087] Further, the Fsss particle size of the binder phase powder is not greater than 4.0 microns, for example, it can be 0.1 micron, 0.2 micron, 0.5 micron, 0.8 micron, 1 micron, 1.2 micron, 1.4 micron, 1.6 micron, 1.8 micron, 2 micron, 2.2 micron, 2.5 micron, 2.8 micron, 3 micron, 3.1 micron, 3.2 micron, 3.5 micron, 3.6 micron, 3.8 micron, 4 micron, etc. Within the micron range, the demand for multi-dimensional powder can be effectively met and the powder adaptability can be increased.
[0088] In some embodiments, the titanium-based cermet spray powder includes, by mass percentage, 35% to 75% Ti(C,N) powder, 10% to 20% (TiM)(C,N) solid solution powder, and 10% to 50% binder phase powder.
[0089] Further, the titanium-based metal ceramic spraying powder includes, by mass percentage, 35% to 75% Ti(C, N) powder, preferably 40% to 70% Ti(C, N) powder, more preferably 45% to 65% Ti(C, N) powder, more preferably 50% to 60% Ti(C, N) powder; 10% to 20% (TiM)(C, N) solid solution powder, preferably 12% to 18% (TiM)(C, N) solid solution powder, more preferably 13% to 17% (TiM)(C, N) solid solution powder; Powder, more preferably 14% to 16% (TiM)(C,N) solid solution powder; 10% to 50% bonding phase powder, preferably 10% to 20% bonding phase powder, more preferably 11% to 18% bonding phase powder, more preferably 12% to 16% bonding phase powder, more preferably 13% to 15% bonding phase powder, preferably 20% to 50% bonding phase powder, more preferably 25% to 45% bonding phase powder, more preferably 30% to 40% bonding phase powder, more preferably 32% to 38% bonding phase powder.
[0090] See also Figure 1 In a second aspect, the present application provides a method for preparing a titanium-based metal ceramic spray powder, comprising:
[0091] S01. Providing a mixed slurry, wherein the mixed slurry includes Ti(C,N) powder, (TiM)(C,N) solid solution powder, and binder phase powder;
[0092] S02, spraying and granulating the mixed slurry to obtain a pre-solidified precursor powder;
[0093] S03, sequentially performing a heating and degreasing stage, a vacuum sintering stage, and a cooling stage on the pre-solid solution precursor powder to obtain a titanium-based metal ceramic block;
[0094] S04, crushing and screening to obtain titanium-based metal ceramic spray powder.
[0095] In the S01:
[0096] In some embodiments, Ti(C,N) powder, (TiM)(C,N) solid solution powder, and binder phase powder are weighed according to the above mass percentages to obtain raw material powder.
[0097] Furthermore, a dispersant and a molding agent are added to the raw material powder, mixed evenly to obtain a prepared raw material, and wet-grinded to obtain a mixed slurry.
[0098] Furthermore, the dispersant includes one or more of dodecylbenzenesulfonic acid, stearic acid and oleic acid.
[0099] Furthermore, the mass fraction of the dispersant to the total amount of raw material powder is 0.1% to 0.5%, for example, it can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, etc.
[0100] Furthermore, the molding agent is one or more of rubber, paraffin and PEG.
[0101] Furthermore, the mass fraction of the molding agent to the total amount of the raw material powder is 2.5% to 4.5%, for example, it can be 2.5%, 3%, 3.5%, 4%, 4.5%, etc.
[0102] Furthermore, the prepared raw materials are added into a grinding carbide or stainless steel ball mill of a ball mill, and a solvent is added and ball milling is performed to obtain a mixed slurry.
[0103] Furthermore, in the mixed slurry, the ratio of solid to liquid is (5-7):(5-3), for example, 5:5, 5.2:4.8, 5.5:4.5, 5.8:4.2, 6:4, 6.2:3.8, 6.5:3.5, 6.8:3.2, 7:3, etc. Within the ratio range, good sphericity can be prepared.
[0104] It will be appreciated that the ratio of solid to liquid is a mass ratio.
[0105] It can be understood that the solid is the raw material powder and the liquid is the ball milling medium.
[0106] Furthermore, the volume mass ratio of the solvent to the total amount of raw material powder is 280ml / Kg to 500ml / Kg, for example, it can be 280ml / Kg, 300ml / Kg, 320ml / Kg, 350ml / Kg, 380ml / Kg, 400ml / Kg, 420ml / Kg, 450ml / Kg, 480ml / Kg, 500ml / Kg, etc.
[0107] Furthermore, during ball milling, 85% to 90% of the total volume of the solvent is first added, for example, 85%, 86%, 87%, 88%, 89%, 90%, etc., and the remaining solvent is added 8h to 10h before the end of ball milling, for example, 8h, 8.5h, 9h, 9.5h, 10h, etc.
[0108] Furthermore, the solvent includes one or more of gasoline, ethylene glycol and hexane.
[0109] Furthermore, the ball mill is a rolling ball mill or a vertical stirring ball mill, the ball diameter of the cemented carbide ball is 6.25mm-12mm, for example, it can be 6.25mm, 6.5mm, 7mm, 7.5mm, 8mm, 8.5mm, 9mm, 9.5mm, 10mm, 10.5mm, 11mm, 11.5mm, 12mm, etc.; the ball-to-material ratio is 2.5:1-10:1, for example, it can be 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1 , 8:1, 8.5:1, 9:1, 9.5:1, 10:1; the ball milling speed is 68-85 rpm, for example, it can be 68 rpm, 70 rpm, 72 rpm, 75 rpm, 78 rpm, 79 rpm, 80 rpm, 82 rpm, 84 rpm, 85 rpm, etc.; the ball milling time is 16h-90h, for example, it can be 16h, 20h, 25h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, 70h, 75h, 80h, 85h, 90h, etc.
[0110] In the S02:
[0111] In some embodiments, the mixed slurry is placed in a spray tower for spray spheroidization granulation.
[0112] Furthermore, the pre-solid solution precursor powder is spherical.
[0113] Furthermore, the inlet temperature in the spray tower is T1, the outlet temperature is T2, the centrifugal atomization speed of the spray spheroidization granulation is v1, and the frequency is f.
[0114] Furthermore, T1 is 180°C to 280°C, for example, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, etc.
[0115] Further, T2 is 100°C to 130°C, for example, it can be 100°C, 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C, 120°C, 122°C, 125°C, 128°C, 130°C, etc.
[0116] Furthermore, v1 is 5500 rpm to 9500 rpm, for example, 5500 rpm, 6000 rpm, 6500 rpm, 7000 rpm, 7500 rpm, 8000 rpm, 8500 rpm, 9000 rpm, 9500 rpm, etc.
[0117] Furthermore, f is 85 Hz to 180 Hz, for example, it can be 85 Hz, 90 Hz, 95 Hz, 100 Hz, 105 Hz, 110 Hz, 115 Hz, 120 Hz, 125 Hz, 130 Hz, 135 Hz, 140 Hz, 145 Hz, 150 Hz, 155 Hz, 160 Hz, 165 Hz, 170 Hz, 175 Hz, 180 Hz, etc.
[0118] In said S03:
[0119] In some embodiments, the heating and degreasing stage is carried out according to the preheating, vacuuming, heating and insulation processes, preheating to T3 temperature, the heating rate does not exceed v2, and the insulation time is t1; vacuuming to below P; heating to T4, the heating rate does not exceed v3, and at T4 temperature, insulation is t2.
[0120] Furthermore, T3 is 80°C to 200°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc.
[0121] v2 does not exceed 10℃ / min, for example, it may be no more than 0.5℃ / min, no more than 1℃ / min, no more than 2℃ / min, no more than 3℃ / min, no more than 4℃ / min, no more than 5℃ / min, no more than 6℃ / min, no more than 7℃ / min, no more than 8℃ / min, no more than 9℃ / min, no more than 10℃ / min, etc.
[0122] t1 is 30 min to 60 min, for example, it can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.
[0123] P is 10 Pa or less, for example, it may be 1 Pa or less, 2 Pa or less, 3 Pa or less, 4 Pa or less, 5 Pa or less, 6 Pa or less, 7 Pa or less, 8 Pa or less, 9 Pa or less, 10 Pa or less, etc.
[0124] T4 is 280°C to 450°C, for example, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 450°C, etc.
[0125] v3 does not exceed 5°C / min, for example, not exceeding 0.5°C / min, not exceeding 1°C / min, not exceeding 2°C / min, not exceeding 3°C / min, not exceeding 4°C / min, not exceeding 5°C / min, etc.
[0126] t2 is 50 min to 120 min, for example, it can be 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, etc.
[0127] In some embodiments, during the vacuum sintering stage, the heating rate does not exceed v4, the heating temperature is increased from T4 to T5, and the temperature is kept at t3 time; the heating rate does not exceed v5, and when the sintering temperature reaches T6, the temperature is kept at t4 time; the heating rate does not exceed v6, and when the sintering temperature reaches T7, the temperature is kept at t5 time; the heating rate does not exceed v7, and when the sintering temperature reaches T8, the temperature is kept at t6 time.
[0128] Furthermore, T4 is 280°C to 450°C, for example, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 450°C, etc.
[0129] T5 is 520°C to 600°C, for example, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, etc.
[0130] v4 does not exceed 5℃ / min, for example, not more than 0.5℃ / min, not more than 1℃ / min, not more than 2℃ / min, not more than 3℃ / min, not more than 3.3℃ / min, not more than 4℃ / min, not more than 4.2℃ / min, not more than 4.5℃ / min, not more than 4.8℃ / min, not more than 5℃ / min, etc.
[0131] v5 does not exceed 4°C / min, for example, not exceeding 0.5°C / min, not exceeding 1°C / min, not exceeding 2°C / min, not exceeding 3°C / min, not exceeding 3.3°C / min, not exceeding 4°C / min, etc.
[0132] T6 is 600°C to 900°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, etc.
[0133] t3 is 10 min to 90 min, for example, it can be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, etc.
[0134] t4 is 50 min to 90 min, for example, it can be 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, etc.
[0135] v6 does not exceed 3.5°C / min, for example, does not exceed 0.5°C / min, does not exceed 1°C / min, does not exceed 2°C / min, does not exceed 3°C / min, does not exceed 3.5°C / min, etc.
[0136] T7 is 900°C to 1250°C, for example, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, etc.
[0137] t5 is 50 min to 150 min, for example, it can be 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, etc.
[0138] v7 does not exceed 3.5℃ / min, for example, does not exceed 0.5℃ / min, does not exceed 1℃ / min, does not exceed 2℃ / min, does not exceed 3℃ / min, does not exceed 3.5℃ / min, etc.
[0139] T8 is 1250°C to 1420°C, for example, it can be 1250°C, 1300°C, 1320°C, 1330°C, 1350°C, 1360°C, 1380°C, 1400°C, 1410°C, 1420°C, etc.
[0140] t6 is 70 min to 210 min, for example, it can be 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min, 180 min, 190 min, 200 min, 210 min, etc.
[0141] It can be understood that the pre-solid solution precursor powder obtained by spray granulation is loaded into a graphite boat mold brushed with non-stick boat coating, and then the graphite boat carrying the spheroidized granulated pre-solid solution precursor powder is loaded into a vacuum sintering furnace, and the heating and degreasing stage, vacuum sintering stage and furnace cooling stage are carried out in sequence, and then the titanium-based metal ceramic block is taken out of the furnace, and the shape of the block is similar to the cavity in the graphite boat.
[0142] It can also be understood that the pre-solidified precursor powder is sintered in a vacuum sintering furnace. After the vacuum sintering stage is completed, the titanium-based metal ceramic block will be cooled down to room temperature along with the vacuum sintering furnace to obtain a titanium-based metal ceramic block.
[0143] In said S04:
[0144] It can be understood that the obtained titanium-based metal ceramic block is placed in the hopper of a double-roll crusher and crushed into powder. The speed adjustment range of the double-roll crusher is 35 to 85 rpm. The crushed powder of the titanium-based metal ceramic block is placed in a multi-layer ultrasonic oscillation screen to classify the powder. The blocks whose particle size cannot meet the screening requirements after classification need to be crushed for the second or third time and then placed in the multi-layer ultrasonic oscillation screen again to classify the powder, and finally the corresponding grade of titanium-based metal ceramic thermal spray powder is obtained.
[0145] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0146] Example 1
[0147] See also Figure 2 , this embodiment provides a titanium-based metal ceramic spray powder, which includes 66% Ti(C, N) powder, 17% (TiWTaNb)(C, N) solid solution powder, and 17% bonding phase powder by mass percentage, and the bonding phase powder includes Co element, Ni element, Mo element and Cr element;
[0148] The Fsss particle size of Ti(C,N) powder is 1.6 μm, the Fsss particle size of (TiWTaNb)(C,N) solid solution powder is 1.2 μm, and the Fsss particle size of binder phase powder is 0.8 μm;
[0149] The preparation method of the titanium-based metal ceramic spray powder comprises:
[0150] Step 1, weigh Ti(C, N) powder, (TiWTaNb)(C, N) solid solution powder and binder phase powder as raw material powders according to the above mass percentages, mix them, add dispersant and molding agent, mix them evenly to obtain a prepared raw material, wherein the dispersant is dodecylbenzenesulfonic acid, the molding agent is PEG, the mass fraction of the dispersant to the total amount of the raw material powder is 0.3%, and the mass fraction of the molding agent to the total amount of the raw material powder is 3.5%;
[0151] Step 2, the prepared raw materials are loaded into the ball mill of the ball mill, and a solvent is added and a cemented carbide ball is added for ball milling to obtain a mixed slurry; wherein, the inner shell of the ball mill is made of cemented carbide as a whole; the solvent is ethylene glycol, and the volume mass ratio of the solvent to the total amount of raw material powder is 350ml / Kg; the ball milling is wet milling, using a rolling ball mill, and 87% of the total volume of the solvent is first added during ball milling, and the remaining solvent is added 9h before the end of ball milling; the cemented carbide ball is cemented carbide YG6X, the diameter of the cemented carbide ball is 8.5mm, the ball-to-material ratio is 6:1, the ball milling speed is 75 rpm, and the ball milling time is 52h;
[0152] Step 3, placing the mixed slurry into a spray tower for spray spheroidization granulation and obtaining a spherical pre-solid solution precursor powder; the inlet temperature setting range of the sprayer is 230° C., the outlet temperature is set to 115° C., the centrifugal atomization speed of the spray granulation is 7500 rpm, and the frequency is 130 Hz;
[0153] Step 4, spray spheroidization and granulation to obtain a spherical pre-solid solution precursor powder into a graphite boat mold brushed with a non-stick boat coating, and then the graphite boat carrying the spheroidized granulated pre-solid solution precursor powder is placed in a vacuum sintering furnace, the heating rate and the insulation time are controlled, and the degreasing stage and the vacuum sintering stage are heated in sequence; after the vacuum sintering is completed, the furnace cooling stage is entered, and then the titanium-based metal ceramic block is taken out of the furnace, and the block shape is similar to the inner cavity of the graphite boat; wherein, the heating and degreasing stage is carried out according to the preheating, vacuuming, heating and insulation procedures, preheating to 140°C, the heating rate does not exceed 5°C / min, insulation for 45 minutes, vacuuming to below 5Pa, heating to 360°C, and heating The speed does not exceed 5℃ / min, and the temperature is kept at 360℃ for 85min; in the vacuum sintering stage, the heating rate does not exceed 3℃ / min, the heating temperature is increased from 360℃ to 560℃, and the holding time is 50min; the heating rate does not exceed 2.5℃ / min, and when the sintering temperature reaches 750℃, it is kept warm for 70min; the heating rate does not exceed 2℃ / min, and when the sintering temperature reaches 1075℃, it is kept warm for 100min; the heating rate does not exceed 2℃ / min, and when the sintering temperature reaches 1350, it is kept warm for 150min; after the vacuum sintering stage is completed, the titanium-based metal ceramic block in the furnace will be cooled with the furnace to room temperature to obtain a titanium-based metal ceramic block.
[0154] Step 5: crushing and sieving the obtained titanium-based metal ceramic block to obtain titanium-based metal ceramic thermal spraying powder.
[0155] Example 2
[0156] This embodiment provides a titanium-based metal ceramic spray powder, which includes 60% Ti(C, N) powder, 20% (TiWTaNb)(C, N) solid solution powder, and 20% bonding phase powder by mass percentage, and the bonding phase powder includes Co element, Ni element, Mo element and Cr element;
[0157] The preparation method of the titanium-based metal ceramic spray powder is the same as that of Example 1.
[0158] Example 3
[0159] This embodiment provides a titanium-based metal ceramic spray powder, which includes 75% Ti(C, N) powder, 10% (TiWTaNb)(C, N) solid solution powder, and 15% bonding phase powder by mass percentage, and the bonding phase powder includes Co element, Ni element, Mo element and Cr element;
[0160] The preparation method of the titanium-based metal ceramic spray powder is the same as that of Example 1.
[0161] Example 4
[0162] See also Figure 3 This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the (TiWTaNb)(C,N) solid solution powder in Example 1 is replaced by (TiW)(C,N), and the rest is the same as Example 1.
[0163] Example 5
[0164] See also Figure 4 This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the (TiWTaNb)(C,N) solid solution powder in Example 1 is replaced by (TiTaNb)(C,N), and the rest is the same as Example 1.
[0165] Example 6
[0166] See also Figure 5 This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the (TiWTaNb)(C,N) solid solution powder in Example 1 is replaced by (TiVZrTaNb)(C,N), and the rest is the same as Example 1.
[0167] Example 7
[0168] See also Figure 6 This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the (TiWTaNb)(C,N) solid solution powder in Example 1 is replaced by (TiWMoVZr)(C,N), and the rest is the same as Example 1.
[0169] Example 8
[0170] See also Figure 7 This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the (TiWTaNb)(C,N) solid solution powder in Example 1 is replaced by (TiCrVZr)(C,N), and the rest is the same as Example 1.
[0171] Example 9
[0172] See also Figure 8This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the bonding phase powder in Example 1 is replaced with Co element and Ni element; the rest is the same as Example 1.
[0173] Example 10
[0174] See also Fig. 9 This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the bonding phase powder in Example 1 is replaced with Co element, Ni element and Mo element; the rest is the same as Example 1.
[0175] Embodiment 11
[0176] This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the bonding phase powder in Embodiment 1 is replaced with Mo element and Cr element; the rest is the same as Embodiment 1.
[0177] Example 12
[0178] This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the bonding phase powder in Embodiment 1 is replaced with Co element; the rest is the same as Embodiment 1.
[0179] Embodiment 13
[0180] This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the bonding phase powder in Embodiment 1 is replaced with Cr element; the rest is the same as Embodiment 1.
[0181] Embodiment 14
[0182] See also Fig.10 This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the Fsss particle size of the Ti(C,N) powder in Example 1 is replaced with 3 microns, the Fsss particle size of the (TiWTaNb)(C,N) solid solution powder is replaced with 2.8 microns, and the Fsss particle size of the bonding phase powder is replaced with 3.2 microns; the rest is the same as Example 1.
[0183] Embodiment 15
[0184] See also Fig.11 This embodiment provides a titanium-based metal ceramic spray powder. In this embodiment, the Fsss particle size of the Ti(C,N) powder in Example 1 is replaced with 0.5 microns, the Fsss particle size of the (TiWTaNb)(C,N) solid solution powder is replaced with 0.8 microns, and the Fsss particle size of the bonding phase powder is replaced with 0.6 microns; the rest is the same as Example 1.
[0185] Example 16
[0186] The present embodiment provides a titanium-based metal ceramic spray powder. In the present embodiment, the Fsss particle size of the Ti(C, N) powder in Example 1 is replaced with 1.6 microns, the Fsss particle size of the (TiWTaNb)(C, N) solid solution powder is replaced with 1.2 microns, and the Fsss particle size of the bonding phase powder is replaced with 0.8 microns; the rest is the same as Example 1.
[0187] Embodiment 17
[0188] This embodiment is basically the same as Embodiment 1, except that, in this embodiment,
[0189] In step 1, the dispersant is stearic acid, the molding agent is paraffin, the mass fraction of the dispersant to the total amount of the raw material powder is 0.1%, and the mass fraction of the molding agent to the total amount of the raw material powder is 2.5%;
[0190] In step 2, the solvent is hexane, and the volume mass ratio of the solvent to the total amount of raw material powder is 280 ml / kg; the ball milling is wet milling, using a rolling ball mill, 85% of the total volume of the solvent is added during ball milling, and the remaining solvent is added 8 hours before the end of ball milling; the cemented carbide ball is cemented carbide YG6X, the diameter of the cemented carbide ball is 6.25 mm, the ball-to-material ratio is 2.5:1, the ball milling speed is 68 rpm, and the ball milling time is 90 hours;
[0191] In step 3, the inlet temperature of the sprayer is set to 180°C, the outlet temperature is set to 100°C, and the centrifugal atomization speed of the spray granulation is 85 Hz, about 9500 rpm;
[0192] In step 4, the heating and debinding stage is carried out according to the preheating, vacuuming, heating and insulation processes, preheating to 80°C, the heating rate does not exceed 10°C / min, insulation for 60 minutes, vacuuming to below 10Pa, heating to 280°C, the heating rate does not exceed 5°C / min, and insulation at 280°C for 120 minutes; in the vacuum sintering stage, the heating rate does not exceed 2.5°C / min, the heating temperature is increased from 280°C to 520°C, and insulation is carried out for 30 minutes; the heating rate does not exceed 4°C / min, and when the sintering temperature reaches 600°C, insulation is carried out for 90 minutes; the heating rate does not exceed 3.5°C / min, and when the sintering temperature reaches 900°C, insulation is carried out for 150 minutes; the heating rate does not exceed 3.5°C / min, and when the sintering temperature reaches 1250°C, insulation is carried out for 210 minutes.
[0193] Embodiment 18
[0194] See also Fig.12 This embodiment is basically the same as Embodiment 1, except that, in this embodiment,
[0195] In step 1, the dispersant is oleic acid, the molding agent is rubber, the mass fraction of the dispersant to the total amount of raw material powder is 0.5%, and the mass fraction of the molding agent to the total amount of raw material powder is 4.5%;
[0196] In step 2, the solvent is gasoline, and the volume mass ratio of the solvent to the total amount of raw material powder is 500 ml / kg; the ball milling is wet milling, using a rolling ball mill, 90% of the total volume of the solvent is first added during ball milling, and the remaining solvent is added 10 hours before the end of ball milling; the cemented carbide ball is cemented carbide YG6X, the diameter of the cemented carbide ball is 12 mm, the ball-to-material ratio is 10:1, the ball milling speed is 85 rpm, and the ball milling time is 16 hours;
[0197] In step 3, the inlet temperature of the sprayer is set to 280°C, the outlet temperature is set to 130°C, and the centrifugal atomization speed of the spray granulation is 180 Hz, about 5500 rpm;
[0198] In step 4, the heating and debinding stage is carried out according to the preheating, vacuuming, heating and insulation processes, preheating to 200°C, the heating rate does not exceed 2°C / min, and the insulation is carried out for 30 minutes. The vacuum is evacuated to below 3Pa, and the temperature is increased to 450°C, the heating rate does not exceed 2°C / min, and the temperature is kept at 450°C for 50 minutes; in the vacuum sintering stage, the heating rate does not exceed 3°C / min, the heating temperature is increased from 450°C to 600°C and the insulation is carried out for 30 minutes; the heating rate does not exceed 2°C / min, and when the sintering temperature reaches 900°C, the insulation is carried out for 50 minutes; the heating rate does not exceed 2.5°C / min, and when the sintering temperature reaches 1250°C, the insulation is carried out for 50 minutes; the heating rate does not exceed 2°C / min, and when the sintering temperature reaches 1420°C, the insulation is carried out for 70 minutes.
[0199] Embodiment 19
[0200] See also Fig.13 , this embodiment provides a titanium-based metal ceramic spray powder, which includes 65% Ti(C,N) powder, 20% (TiCrMo)(C,N) solid solution powder, and 15% bonding phase powder by mass percentage, and the bonding phase powder includes Co element, Ni element, Mo element and Cr element;
[0201] The Fsss particle size of Ti(C,N) powder is 2.2 μm, the Fsss particle size of (TiCrMo)(C,N) solid solution powder is 2.6 μm, and the Fsss particle size of binder phase powder is 1.8 μm;
[0202] The preparation method of the titanium-based metal ceramic spray powder comprises:
[0203] Step 1, weighing Ti(C,N) powder, (TiCrMo)(C,N) solid solution powder and binder phase powder as raw material powders according to the above mass percentages, mixing them, adding a dispersant and a molding agent, and mixing them evenly to obtain a prepared raw material, wherein the dispersant is dodecylbenzenesulfonic acid, the molding agent is PEG, the mass fraction of the dispersant to the total amount of the raw material powder is 0.3%, and the mass fraction of the molding agent to the total amount of the raw material powder is 3.5%;
[0204] Step 2, the prepared raw materials are loaded into the ball mill of the ball mill, and a solvent is added and a cemented carbide ball is added for ball milling to obtain a mixed slurry; wherein, the inner shell of the ball mill is made of cemented carbide as a whole; the solvent is ethylene glycol, and the volume mass ratio of the solvent to the total amount of raw material powder is 350ml / Kg; the ball milling is wet milling, using a rolling ball mill, and 87% of the total volume of the solvent is first added during ball milling, and the remaining solvent is added 9h before the end of ball milling; the cemented carbide ball is cemented carbide YG6X, the diameter of the cemented carbide ball is 8.5mm, the ball-to-material ratio is 6:1, the ball milling speed is 75 rpm, and the ball milling time is 52h;
[0205] Step 3, placing the mixed slurry into a spray tower for spray spheroidization granulation to obtain a spherical pre-solid solution precursor powder; the inlet temperature setting range of the sprayer is 230° C., the outlet temperature is set to 115° C., and the centrifugal atomization speed of the spray granulation is 130 Hz, about 7500 rpm;
[0206] Step 4, spray spheroidization and granulation to obtain a spherical pre-solid solution precursor powder into a graphite boat mold brushed with a non-stick boat coating, and then the graphite boat carrying the spheroidized granulated pre-solid solution precursor powder is placed in a vacuum sintering furnace, the heating rate and the insulation time are controlled, and the degreasing stage and the vacuum sintering stage are heated in sequence; after the vacuum sintering is completed, the furnace cooling stage is entered, and then the titanium-based metal ceramic block is taken out of the furnace, and the block shape is similar to the inner cavity of the graphite boat; wherein, the heating and degreasing stage is carried out according to the preheating, vacuuming, heating and insulation procedures, preheating to 140°C, the heating rate does not exceed 5°C / min, insulation for 45 minutes, vacuuming to below 5Pa, heating to 360°C, and heating The speed does not exceed 5℃ / min, and the temperature is kept at 360℃ for 85min; in the vacuum sintering stage, the heating rate does not exceed 5℃ / min, the heating temperature is increased from 360℃ to 560℃, and the temperature is kept for 60min; the heating rate does not exceed 4℃ / min, and when the sintering temperature reaches 750℃, it is kept for 70min; the heating rate does not exceed 3.5℃ / min, and when the sintering temperature reaches 1075℃, it is kept for 100min; the heating rate does not exceed 3.5℃ / min, and when the sintering temperature reaches 1250, it is kept for 140min; after the vacuum sintering stage is completed, the titanium-based metal ceramic block in the furnace will be cooled with the furnace to room temperature to obtain a titanium-based metal ceramic block.
[0207] Step 5: crushing and sieving the obtained titanium-based metal ceramic block to obtain titanium-based metal ceramic thermal spraying powder.
[0208] Embodiment 20
[0209] This embodiment provides a titanium-based metal ceramic spray powder, which includes, by mass percentage, 60% Ti(C, N) powder, 15% (TiVZrTaNb)(C, N) solid solution powder, and 25% bonding phase powder, wherein the bonding phase powder includes Co element, Ni element, Mo element, and Cr element;
[0210] The preparation method of the titanium-based metal ceramic spray powder is the same as that of Example 1.
[0211] Embodiment 21
[0212] This embodiment provides a titanium-based metal ceramic spray powder, which includes 50% Ti(C, N) powder, 20% (TiWTaNb)(C, N) solid solution powder, and 30% bonding phase powder by mass percentage, and the bonding phase powder includes Co element, Ni element, Mo element and Cr element;
[0213] The preparation method of the titanium-based metal ceramic spray powder is the same as that of Example 1.
[0214] Embodiment 22
[0215] This embodiment provides a titanium-based metal ceramic spray powder, which includes, by mass percentage, 45% Ti(C, N) powder, 15% (TiWVZr)(C, N) solid solution powder, and 40% bonding phase powder, wherein the bonding phase powder includes Co element, Ni element, Mo element, and Cr element;
[0216] The preparation method of the titanium-based metal ceramic spray powder is the same as that of Example 1.
[0217] Embodiment 23
[0218] This embodiment provides a titanium-based metal ceramic spray powder, which includes, by mass percentage, 40% Ti(C, N) powder, 15% (TiWTaNb)(C, N) solid solution powder, and 45% bonding phase powder, wherein the bonding phase powder includes Co element, Ni element, Mo element, and Cr element;
[0219] The preparation method of the titanium-based metal ceramic spray powder is the same as that of Example 1.
[0220] Embodiment 24
[0221] This embodiment provides a titanium-based metal ceramic spray powder, which includes, by mass percentage, 35% Ti(C, N) powder, 15% (TiWMoVZr)(C, N) solid solution powder, and 50% bonding phase powder, wherein the bonding phase powder includes Co element, Ni element, Mo element, and Cr element;
[0222] The preparation method of the titanium-based metal ceramic spray powder is the same as that of Example 1.
[0223] The titanium-based metal ceramic thermal spray powder and the preparation method thereof provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. Titanium-based metal ceramic spray powder, characterized in that: It includes Ti(C,N) powder, (TiM)(C,N) solid solution powder, and bonding phase powder, wherein M includes at least one of W, Mo, Cr, V, Zr, Ta, and Nb elements.
2. The titanium-based metal ceramic spraying powder according to claim 1, characterized in that: The bonding phase powder includes one or more elements of Co, Ni, Mo, and Cr.
3. The titanium-based metal ceramic spraying powder according to claim 1, characterized in that: The Ti(C,N) powder has a Fsss particle size of not greater than 4.0 microns; and / or The (TiM)(C,N) solid solution powder has a Fsss particle size of not more than 4.0 microns; and / or The Fsss particle size of the binder phase powder is no greater than 4.0 microns.
4. The titanium-based metal ceramic spraying powder according to claim 1, characterized in that: The titanium-based metal ceramic spray powder includes 35% to 75% Ti(C,N) powder by mass percentage. 10% to 20% (TiM) (C, N) solid solution powder, 10% to 50% binder phase powder.
5. A method for preparing titanium-based metal ceramic spray powder, characterized in that: include: Providing a mixed slurry, the mixed slurry comprising Ti(C,N) powder, (TiM)(C,N) solid solution powder, and a binder phase powder; Spray granulate the mixed slurry to obtain pre-solidified precursor powder; The pre-solid solution precursor powder is subjected to a heating and degreasing stage, a vacuum sintering stage and a cooling stage in sequence to obtain a titanium-based metal ceramic block; The titanium-based metal ceramic spray powder is obtained by crushing and screening.
6. The method for preparing titanium-based metal ceramic spray powder according to claim 5, characterized in that: Weigh Ti(C,N) powder, (TiM)(C,N) solid solution powder, and binder phase powder according to the above mass percentage to obtain raw material powder, add a dispersant and a molding agent to the raw material powder, mix them evenly to obtain a prepared raw material, and wet grind to obtain a mixed slurry; and / or The mixed slurry is placed in a spray tower for spray spheroidization granulation, the inlet temperature of the spray tower is T1, the outlet temperature is T2, the centrifugal atomization speed of the spray spheroidization granulation is v1, the frequency is f, and the pre-solid solution precursor powder is spherical; and / or The heating and degreasing stage is carried out according to the preheating, vacuuming, heating and insulation procedures, preheating to T3 temperature, the heating rate does not exceed v2, and the insulation time is t1; vacuuming to below P; heating to T4, the heating rate does not exceed v3, and at T4 temperature, insulation time t2; and / or During the vacuum sintering stage, the heating rate does not exceed v4, the heating temperature rises from T4 to T5, and is kept warm for t3 time; the heating rate does not exceed v5, when the sintering temperature reaches T6, it is kept warm for t4 time; the heating rate does not exceed v6, when the sintering temperature reaches T7, it is kept warm for t5 time; the heating rate does not exceed v7, when the sintering temperature reaches T8, it is kept warm for t6 time.
7. The method for preparing titanium-based metal ceramic spray powder according to claim 6, characterized in that: The prepared raw materials are added into the grinding carbide or stainless steel ball mill of the ball mill, and the solvent is added and ball milled to obtain a mixed slurry.
8. The method for preparing titanium-based metal ceramic spray powder according to claim 6, characterized in that: T1 is 180°C to 280°C; and / or T2 is 100°C to 130°C; and / or v1 is 5500 rpm to 9500 rpm; and / or f is between 85 Hz and 180 Hz; and / or T3 is 80°C to 200°C; and / or v2 does not exceed 10℃ / min; and / or t1 is 30 min to 60 min; and / or P is less than 10Pa; and / or T4 is 280°C to 450°C; and / or v3 does not exceed 5℃ / min; and / or t2 is 50 min to 120 min; and / or T5 is 520°C to 600°C; and / or v4 does not exceed 5℃ / min; and / or v5 does not exceed 4℃ / min; and / or T6 is 600°C to 900°C; and / or t3 is 10 min to 90 min; and / or t4 is 50 min to 90 min; and / or v6 does not exceed 3.5℃ / min; and / or T7 is 900°C to 1250°C; and / or t5 is 50 min to 150 min; and / or v7 does not exceed 3.5℃ / min; and / or T8 is 1250°C to 1420°C; and / or t6 is 70min~210min.
9. The method for preparing titanium-based metal ceramic spray powder according to claim 7, characterized in that: The dispersant comprises one or more of dodecylbenzenesulfonic acid, stearic acid and oleic acid; and / or The molding agent is one or more of rubber, paraffin and PEG; and / or The solvent includes one or more of gasoline, ethylene glycol and hexane.
10. The method for preparing titanium-based metal ceramic spray powder according to claim 7, characterized in that: In the mixed slurry, the ratio of solid to liquid is (5-7):(5-3); and / or The mass fraction of the dispersant in the total amount of the raw material powder is 0.1% to 0.5%; and / or The mass fraction of the molding agent to the total amount of raw material powder is 2.5% to 4.5%; and / or The volume mass ratio of the solvent to the total amount of the raw material powder is 280ml / Kg to 500ml / Kg; and / or During ball milling, 85% to 90% of the total volume of the solvent is first added, and the remaining solvent is added 8 to 10 hours before the end of ball milling; and / or The ball mill is a rolling ball mill or a vertical stirring ball mill, the diameter of the carbide balls is 6.25 mm to 12 mm, the ball-to-material ratio is 2.5:1 to 10:1, the ball milling speed is 68 to 85 rpm, and the ball milling time is 16 h to 90 h.
Citation Information
Cited By
Ceramic powder coating and preparation method thereof
CN121064696A